To beg or to freeze: multimodal sensory integration directs behavior in a tadpole - Stynoski, Jennifer Lynn (2012)
Effective coordination of behaviors such as foraging and avoiding predators requires an assessment of cues provided by other organisms. Integrating cues from multiple sensory modalities may enhance the assessment. We studied cue integration by tadpoles of Oophaga pumilio, which live in small arboreal water pools. In this species, mothers periodically visit their tadpoles and feed them with unfertilized eggs. When mothers visit, tadpoles beg conspicuously by vibrating until fed. However, animals other than mother frogs including potential predators may visit water pools. Thus, when a visitor appears, tadpoles must use visitor cues to decide whether to beg or to remain inactive to avoid predation. To elucidate the cues that prompt these behaviors, we videotaped behavior of O. pumilio tadpoles in response to isolated and multimodal cues. Tadpoles swam more when exposed to visual or visual and chemical cues of adult O. pumilio but only exhibited begging when exposed to visual, chemical, and tactile cues together. Visual, chemical, and tactile cues from either male or female adult O. pumilio stimulated swim- ming and begging, but the same cues from similarly sized heterospecific frogs did not. Lastly, tadpoles exposed to a potential predator did not beg and swam less than tadpoles with no stimulus. Together, these findings suggest that O. pumilio tadpoles use multimodal cues to modulate swimming behavior accordingly in the presence of egg provisioners, predators, and other visitors and that tadpole begging is induced by multimodal cues of conspecific frogs such that tactile and perhaps chemical cues supplement visual cues.